2016
DOI: 10.1007/s00167-016-4112-3
|View full text |Cite
|
Sign up to set email alerts
|

Does computer-assisted surgery influence survivorship of cementless total knee arthroplasty in patients with primary osteoarthritis? A 10-year follow-up study

Abstract: Therapeutic, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…a Misc. b 8 years 94.8% ( n = 354) 94.9% ( n = 2836) < 65 years 93.6% ( n = 126) < 65 years 92.4% ( n = 955) Baumbach [ 18 ] 2016 Not stated Aesculap Search prosthesis 10 years 98% ( n = 50) 87% ( n = 46) Ouanezar [ 40 ] 2016 Amplivision Cementless mobile-bearing SCORE - Amplitude 10 years 91% ( n = 87) 86% ( n = 51) Song [ 39 ] 2016 Orthopilot e.motion Braun 9 years 100% ( n = 37) 95.3% ( n = 38) De Steiger [ 51 ] 2015 Multiple Multiple 9 years 95.4% 94.8% < 65 years 93.7% < 65 years 92.2% Cip [ 41 ] 2014 BrainLab Next Gen Mobile bearing and PS Flex 5.5 years 98.9% ( n = 74) 95.4% ( n = 79) a Prosthesis brands (AGC, Duracon, e.motion, LCS complete, and Profix) b Navigation systems (Brainlab, Orthopilot, and Stryker) CAS Computer-assisted TKA, CON Conventional TKA, KSS Knee Society Score, HSS Hospital for Special Services Score, SF-36 Short-form 36, OKS Oxford knee score, WOMAC Western Ontario and McMaster Universities osteoarthritis index …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a Misc. b 8 years 94.8% ( n = 354) 94.9% ( n = 2836) < 65 years 93.6% ( n = 126) < 65 years 92.4% ( n = 955) Baumbach [ 18 ] 2016 Not stated Aesculap Search prosthesis 10 years 98% ( n = 50) 87% ( n = 46) Ouanezar [ 40 ] 2016 Amplivision Cementless mobile-bearing SCORE - Amplitude 10 years 91% ( n = 87) 86% ( n = 51) Song [ 39 ] 2016 Orthopilot e.motion Braun 9 years 100% ( n = 37) 95.3% ( n = 38) De Steiger [ 51 ] 2015 Multiple Multiple 9 years 95.4% 94.8% < 65 years 93.7% < 65 years 92.2% Cip [ 41 ] 2014 BrainLab Next Gen Mobile bearing and PS Flex 5.5 years 98.9% ( n = 74) 95.4% ( n = 79) a Prosthesis brands (AGC, Duracon, e.motion, LCS complete, and Profix) b Navigation systems (Brainlab, Orthopilot, and Stryker) CAS Computer-assisted TKA, CON Conventional TKA, KSS Knee Society Score, HSS Hospital for Special Services Score, SF-36 Short-form 36, OKS Oxford knee score, WOMAC Western Ontario and McMaster Universities osteoarthritis index …”
Section: Resultsmentioning
confidence: 99%
“…In a smaller study of 135 knees with 10 year follow-up, there was a trend towards a higher rate of revision in non-navigated TKA using an uncemented prosthesis. This was explained by increased rates of secondary patella resurfacing being required in the conventional group [ 40 ]. Kim et al [ 49 ] demonstrated 98% survivorship in both conventional and CAS TKA in patients under 65% with minimum 14 years follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies considered that asymmetric alignment could lead to abnormal stress on the surfaces of weight-bearing, further resulting in aseptic failure or bone collapse. 2,33,34 However, Parratte et al found that mechanical alignment within AE3 degrees from neutral mechanical axis was of little practical value, 35 and as described by Kim et al 36 and Ouanezar et al, 37 the improved implant alignments within CAS may not result in better implant survivorship after !10 years. Unfortunately, we could hardly obtain sufficient data from the included studies to conduct the relevant meta-analysis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAS in TKA may ensure better postoperative alignment of the leg, adequate soft tissue balancing, and proper implant position as compared with TKA performed using a conventional technique and it would be more helpful in cases of severe deformity or limited knee motion [ 30 , 31 , 32 , 33 ]. It is also expected that this improved accuracy may lead to better clinical results and reduced revision rates [ 34 , 35 ]. Moreover, since CAS system avoids intramedullary instrumentation, it may decease postoperative bleeding and thromboembolic complication [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%